Controllable chiral behavior of type‐II core/shell quantum dots adjusted by shell thickness and coordinated ligands. Issue 4 (19th January 2021) - Shao, Xiao; Zhang, Tianyong; Li, Bin; Wu, Yue; Li, Siyi; Wang, Jingchao; Jiang, Shuang
Abstract: Chiral semiconductor nanomaterials induced by capped chiral ligands are of great interest for both theoretical studies and advanced applications. In this study, CdTe/CdSe quantum dots (QDs), defined as type‐II core/shell nanostructure, with the advantage of a good separation of holes and electrons are imparted chirality with L/D‐cysteine and L/D‐penicillamine molecules. Circular dichroism (CD) at exciton transitions from cysteine‐ and penicillamine‐capped QDs is different in shape and intensity. CD intensities decrease with increasing shell thickness from three monolayers to six monolayers, indicating a decreased hybridization degree between the holes in CdTe core and the electrons in chiral ligands. Elevated cysteine concentration leads to decreased g‐factor, probably due to an altered binding mode from tridentate to bidentate. Our observations provide further insights into the understanding of chiral phenomenon as well as optimized design and applications of chiral nanostructures. Abstract : Type‐II core/shell nanostructure, CdTe/CdSe quantum dots (QDs), has been capped with chiral ligands, L/D‐Cystein/penicillamine, to achieve chirality with clear circular dichroism (CD) signals. The chiral intensity is controllable through changing the shell thickness. Considering the good separation degree of holes and electrons of type‐II core/shell nanostructures, the decreased g‐facor with the increased shell thickness indicated the hybridization degree between hole in CdTe core and electron in chiral ligands decrease.